Hubungan Sikap Terhadap Pemberian Asi Esklusif Di Wilayah Kerja Puskesmas Buntu Batu Kabupaten Enrekang - Laela, Nur; Hamdiyah, Hamdiyah; Nurbaya, St; Ibrahim, Ibrahim; Kassaming, Kassaming; Tahir, Muhammad (Diagnosis Jurnal Ilmiah Kesehatan, 2023)
Exclusive breastfeeding is good nutrition to protect babies against infection and prevent malnutrition because it contains nutrients needed by the baby's body. Breastfeeding is related to the low level of knowledge about exclusive breastfeeding and there are still many mothers who do not understand the importance of colostrum. Mothers throw away colostrum or milk that comes out first because it is still considered excrement from breast milk, even though colostrum contains lots of nutrients and immune substances for the body. This type of research uses a cross sectional design. The population of this study were mothers who had babies > 6-12 months as many as 94 babies in the Buntu Batu Health Center, Buntu Batu District. The sample in this study were mothers who had babies >6-12 months as many as 94 babies at the Buntu Batu Health Center using total sampling, i.e. all populations were sampled. There is a relationship between attitudes towards exclusive breastfeeding in the Working Area of the UPT Puskesmas Buntu Batu, Enrekang Regency, with a 95% confidence level, a p-value = 0.003 is obtained, which means it is smaller than the α-value (P <0.05).